Hemodynamic impact of blood viscosity in intracranial atherosclerotic arteries with varying stenosis severity: A non-newtonian computational fluid dynamics patient specific study - Lei Zhengyao; Muhammad Nor Ikmal Muhamad Nazri; Adi Azriff Basri; Masaaki Tamagawa; Kaito Sagara; Abdul Hanif Khan Yusof Khan; Eusni Rahayu Mohd Tohit (PLoS ONE, 2026)
Intracranial atherosclerotic stenosis (ICAS) is a major cause of ischemic stroke, yet geometric stenosis alone may not fully reflect the functional hemodynamic burden of a lesion. This study used computational fluid dynamics (CFD) with a shear-thinning non-Newtonian Carreau viscosity model to quantify the combined effects of stenosis severity and blood viscosity on intracranial hemodynamics. A middle cerebral artery (MCA) stenosis model with an original ~70% narrowing was reconstructed from computed tomography angiography, and additional idealized stenosis variants (30%, 50%, and 90%) were generated on the same anatomical background to enable controlled comparisons. Three viscosity states (below-normal, normal, and high) were simulated under transient, incompressible, laminar flow with rigid walls and identical boundary conditions. Velocity, pressure, and wall shear stress (WSS), oscillatory shear index (OSI) and time-averaged wall shear stress (TAWSS) were evaluated. The results show that flow behavior is governed by the combined influence of geometry and rheology, rather than by stenosis severity alone. Severe stenosis produced a dual pathological shear environment, characterized by elevated WSS within the stenotic region and disturbed low-shear flow downstream. In addition, TAWSS showed a non-monotonic response, increasing up to 70% stenosis and then decreasing at 90% stenosis. OSI also showed viscosity-dependent elevation under severe stenosis, with values ranging from approximately 0.38 to 0.48, indicating enhanced oscillatory and disturbed flow.These findings support integrating non-Newtonian hemorheology and hemodynamic metrics with geometric assessment to improve ICAS risk stratification and inform hemodynamics-guided intervention timing.